ANALYSIS FACTORS OF AFFECTING CAPITAL STRUCTURE WITH FIRM SIZE AS MODERATING VARIABLE IN CONSUMER GOODS COMPANIES LISTED ON BEI - Anum, Fatima (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of this research was to examine and to analyze the influence of profitability, sales growth, asset structure, liquidity, operating leverage, and business risk on capital structure simultaneously and partially and whether firm size could moderate the correlation of profitability, sales growth, asset structure, liquidity, operating leverage, and business risk with capital structure. The research objects were consumer goods companies listed in BEI (Indonesia Stock Exchange) in the period of 2012-2015. The research used causality method. The population and the samples were 33 so that there were 132 observation units. The data were analyzed by using multiple linear regression analysis and residual analysis. The result of the first hypothesis showed that simultaneously the independent variables (profitability, sales growth, asset structure, liquidity, operating leverage, and business risk) had significant influence on capital structure. Partially, sales growth, asset structure, liquidity, and operating leverage had significant influence on capital structure, while profitability and business risk did not have any significant influence on capital structure. The result of the second hypothesis showed that firm size could not moderate the correlation of profitability, sales growth, asset structure, liquidity, operating leverage, and business risk with capital structure in consumer goods companies listed in BEI in the period of 2012-2015.